Compassion within conflict: Toward a computational theory of social groups informed by maternal brain physiology. (7th July 2022) - Ho, S. Shaun; Rosenthal, Richard N.; Fox, Helen; Garry, David; Gopang, Meroona; Rollins, Mikaela J.; Soliman, Sarah; Swain, James E.
Abstract: Benevolent intersubjectivity developed in parent–infant interactions and compassion toward friend and foe alike are non-violent interventions to group behavior in conflict. Based on a dyadic active inference framework rooted in specific parental brain mechanisms, we suggest that interventions promoting compassion and intersubjectivity can reduce stress, and that compassionate mediation may resolve conflicts.